Genre Classification of Traditional Malay Music Using Spectrogram Correlation - A. Samad, S.; B. Huddin, A. (International Journal of Engineering and Technology, 2018)
A method to classify the genre of traditional Malay music using spectrogram correlation is described.Â  The method can be divided into three distinct parts consisting of spectrogram construction that retains the most salient feature of the music, template construction that takes into account the variations in music within a genre as well as the music progresses, and template matching based on spectrogram image cross-correlation with unconstrained minimum average correlation energy filters. Experiments conducted with seven genres of traditional Malay music show that the recognition accuracy is dependent on the number of segments used to construct the filter templates, which in turn is related to the length of music segment used. Despite using a small dataset, an average recognition rate of 61.8 percent was obtained for music segments lasting 180 seconds using six relatively short excerpts.Â Â